Anaesthetic management of emergency caesarean section with isolated cortical vein thrombosis and subacute intracerebral haemorrhage. Issue 1 (5th June 2020) - Robson, M.; Higgins, N.; Evans, E.
Summary: We report the case of an emergency caesarean section 5 days following the onset of a right‐sided hemiparesis due to an intracerebral haemorrhage. Computerised tomography imaging in the postoperative period revealed an isolated cortical vein thrombosis as the likely cause. The caesarean section was conducted under general anaesthesia following consideration of the risks and benefits and discussion of these with the patient. No peri‐operative complications occurred and neuro‐rehabilitation was commenced as an inpatient. This case highlights the importance of maintaining a targeted systolic blood pressure whilst avoiding increased intracranial pressure in the obstetric patient with an intracerebral haemorrhage, and that the mode and conduct of anaesthesia can have a profound impact on these measurements. To our knowledge, this is the first reported case of a patient having an emergency caesarean section after subacute intracerebral haemorrhage caused by an isolated cortical vein thrombosis and it demonstrates that general anaesthesia can be used safely in this context. In this complex obstetric case, the role of multidisciplinary team collaboration in the peri‐operative period was essential to optimising the patient's outcome.